Malaysia : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Malaysia. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2018)
This 2018 Article IV Consultation highlights that the Malaysian economy has shown resilience in recent years despite external shocks and has continued to perform well. Progress was made toward achieving high income status and improving inclusion. Median household income has risen further and the already-low national poverty ratio declined. Real GDP growth has surprised on the upside in 2017, and is estimated at 5.8 percent for the year, driven by domestic demand and robust exports. Growth is projected to start to decelerate from its 2017 peak, remaining above potential at 5.3 percent in 2018, and converging to its potential rate of close to 5 percent in the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet